Microsurgical techniques in obstructed semen tract reconstruction - Beharka, Rastislav; Pacík, Dalibor (Abstracts of the 3rd Czech and International Congress of Andrology, 2008)
The main purpose of announcement is to bring the information about possibilities of surgical reconstruction seminal ways obstruction azoospermia inductive. The authors bring the survey of possible solutions based on the ground of information from publication in reviewed technical literature. The possibilities of performance the vasovasoanastomosis and vasoepididymoanastomosis, their techniques, effectiveness and results are presented in the well-arranged announcement. Microsurgical reconstruction results in the restoration of spermatozoa to the ejaculate in 58-97% of cases. The return of spermatozoa to the ejaculate may provide the couple with an opportunity to conceive naturally or through assisted reproduction.